2008
DOI: 10.1089/lap.2007.0130
|View full text |Cite
|
Sign up to set email alerts
|

Transabdominal Preperitoneal Laparoscopic Approach for the Treatment of Sportsman's Hernia

Abstract: The transabdominal preperitoneal laparoscopic approach is safe and feasible in the diagnosis and treatment of Sportsman's hernia, enabling a full return to sports activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…Although, according to general opinion, only 10 mm and bigger trocar site defects should be closed, the development of incisional hernia with consequences was described even with 3-5-mm trocars [59][60][61][62][63][64][65].…”
Section: Port-site Closure Statements Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, according to general opinion, only 10 mm and bigger trocar site defects should be closed, the development of incisional hernia with consequences was described even with 3-5-mm trocars [59][60][61][62][63][64][65].…”
Section: Port-site Closure Statements Recommendationsmentioning
confidence: 99%
“…Felix et al [33] found an occult femoral hernia incidence of 9% in his 1996 series of laparoscopic repair of recurrent inguinal hernia. Mikkelsen et al found the risk of femoral hernia to be 15 times higher after inguinal hernia repair than in the general population, and Chan believes prior inguinal hernia repair may precipitate femoral hernia [65,66]. He found that 50.9% of his series of 225 femoral hernia repairs had concurrent inguinal hernia and 18.2% had prior groin hernia repair.…”
Section: Tapp and Tep Repair And The Occult Synchronous Hernias Statmentioning
confidence: 99%
See 1 more Smart Citation
“…25,32,33 Given that most athletes are concerned about recovery time after surgery, 22 the laparoscopic approach may be the more suitable approach. 28 Other approaches such as TAPP repairs may be equivalent in terms of outcomes 32,34 ; however, TEP may offer advantages such as less pain 20 and lower risk of injury to intraabdominal viscera; TEP may be challenging or inappropriate in other circumstances, as in patients with previous abdominal surgery or the need for prostate surgery. 35 Further developments, especially in relation to cosmesis, include single-port surgery but may take longer to perform than standard TEP repairs.…”
Section: Discussionmentioning
confidence: 99%
“…The exact pathophysiology is unclear and various theories have emerged in literature considering the presences of an occult hernia, a tear or microtears in the transversalis fascia or muscle strain. The theory that posterior weakness in the inguinal wall is the prime cause of groin pain in athletes is supported by the fact that reinforcement of the posterior wall often resolves the groin pain (Malycha & Lovell, 1992;Paajanen et al, 2004;van Veen et al, 2007;Ziprin et al, 2008). Sportmen hernia are found almost exclusively in men and only sporadically in women (Hackney, 1993;Moeller, 2007).…”
Section: Sportsmen Herniamentioning
confidence: 99%